Humor and Wisdom (Content Analysis of Dakwah by Das'ad Latif on Instagram) - Alfauzie, Risaldi; Husain, Wahyuni; A, Aswan; Mahmud, Adilah (Palakka : Media and Islamic Communication, 2023)
This research aims to determine (1) Das'ad Latif's profile, (2) humor in Dakwah by Das'ad Latif on Instagram, and (3) wisdom in Dakwah by Das'ad Latif on Instagram. This study utilizes content analysis with a descriptive technique and a qualitative approach. To collect data, the researcher employed observation and documentation methods. The results of this study indicate that Das'ad Latif frequently discusses women in his Dakwah due to their occasional inability to maintain proper behavior and morals, which should govern their conduct. On his Instagram account, humorous Dakwah messages containing morals were found, consisting of 5 messages, including morals towards others, morals towards parents, and morals towards partners. In these humorous Dakwah messages, there were 3 Dakwah videos discussing women: "Pertanyaan Dongok," in which the word "ibu" (mother) was mentioned 25 times and "istri" (wife) 7 times, "Tips Hadapi Omelan Istri," mentioning "istri" 5 times, and "Kita yang Cicil Dia yang Ambil," mentioning "istri" 5 times and "ibu" 6 times. Meanwhile, the wisdom-based Dakwah messages included 3 messages related to "akidah" (faith), such as "Allah Maha Penyayang" (Allah is the Most Compassionate), "percaya akan kuasa Allah" (belief in the power of Allah), and "keyakinan terhadap takdir Allah" (belief in Allah's destiny). There was 1 message related to "syariah" (Islamic law), namely "siyasah" (politics), and 2 messages related to "akhlak" (morals), focusing on morals towards others.